Effect of saturation on the characteristics of P-wave and S-wave propagation in nearly saturated soils using bender elements. Issue 145 (June 2021) - Gu, Xiaoqiang; Zuo, Kangle; Tessari, Anthony; Gao, Guangyun
Abstract: Theoretical and experimental studies are carried out to investigate the characteristics of P-wave and S-wave propagation in soils with different degrees of saturation, which is quantified using Skempton's B -value. Based on the assumption of homogeneous pore fluid and Biot's theory, the characteristics of elastic wave propagation in nearly saturated soils are obtained and the effects of confining pressure, degree of saturation, and excitation frequency on the wave velocities are analyzed. It is found that the evolutions of P-wave, Biot-wave, and S-wave velocities with the degree of saturation are quite different. In experimental bender element tests, the P-wave signal in nearly saturated soil contains two parts. It is inferred that the first part of the P-wave signal is the fast P-wave component and the second part is a Biot-wave (i.e. slow P-wave of the second kind) as their characteristics agree well with theoretical predictions. It is also found that the relationship between the P-wave velocity, V p, and the B -value depends on the characteristics of the pore fluid. For a pore fluid with de-aired water, the measured V p is independent of the B -value, which is contrary to theoretical predictions. However, for a pore fluid consisting of tap water (i.e. water with air bubbles), the measured V p generally increases with the B -value as predicted, and the relationship between the measured V p and B -value agrees well with the prediction curve when the B -value is smaller than 0.85. When the B -value is larger than 0.85, the measured P-wave velocity is higher than the theoretical prediction, which is probably due to the non-uniform distribution of air bubbles in the pore fluid. Highlights: Theoretical and experimental works are conducted to study the characteristics of elastic waves in nearly saturated sand. The tests indicate that the first part of the P-wave signal is the fast P-wave component and the second part is a Biot-wave. The relationship between V p and the B -value depends on the pore fluid type. The non-homogeneous distribution of air bubbles in pore fluid significantly affects the P-wave velocity.